2003
DOI: 10.1097/00000542-200307000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Systemically Administered α2-Agonist-induced Peripheral Vasoconstriction in Humans

Abstract: The results of this study are the first to characterize the lower end of the dose-response curve for vasoconstriction induced by dexmedetomidine. By denervating the vascular bed of interest or by decreasing sympathetic nervous system activity, the authors were able to observe vasoconstriction induced by a systemically administered alpha(2)-agonist with minimal interference from the sympatholytic effects of the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
128
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(137 citation statements)
references
References 12 publications
6
128
0
3
Order By: Relevance
“…This was administered via TCI. A Harvard Model 22 syringe pump (Harvard Apparatus) connected to a portable computer running STANPUMP software (by Steven L. Schafer, MD, available at http://www.opentci.org/doku.php?idϭcode:code) and the pharmacokinetic parameters of Talke (2003) were used. In Session 1, the infusion was started at a target (plasma) concentration of 1.0 ng/ml, followed first by a 0.5 ng/ml target concentration increase, and then by subsequent 0.25 ng/ml increases thereafter (i.e., 1.0 to 1.5, 1.5 to 1.75, 1.75 to 2.0, and 2.0 to 2.25 ng/ml) until LOC was achieved.…”
Section: Anesthesia Sessionsmentioning
confidence: 99%
“…This was administered via TCI. A Harvard Model 22 syringe pump (Harvard Apparatus) connected to a portable computer running STANPUMP software (by Steven L. Schafer, MD, available at http://www.opentci.org/doku.php?idϭcode:code) and the pharmacokinetic parameters of Talke (2003) were used. In Session 1, the infusion was started at a target (plasma) concentration of 1.0 ng/ml, followed first by a 0.5 ng/ml target concentration increase, and then by subsequent 0.25 ng/ml increases thereafter (i.e., 1.0 to 1.5, 1.5 to 1.75, 1.75 to 2.0, and 2.0 to 2.25 ng/ml) until LOC was achieved.…”
Section: Anesthesia Sessionsmentioning
confidence: 99%
“…In the present study, total intravenous anesthesia with propofol and remifentanil combined with dexmedetomidine maintained HR at a lower level, reduced bleeding and improved surgical satisfaction scores. In addition, unlike anesthetic drugs which dilate blood vessels, dexmedetomidine constricts peripheral arteries and veins (27). Although there is no clear clinical evidence that dexmedetomidine can contract blood vessels in the nasal mucosa, it is not ruled out that reducing bleeding may be associated with vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…Same authors in another experimental study reported that clinically relevant doses of dexmedetomidine enhanced blockade when added to ropivacaine 13 . Dexmedetomidine may lead to side effects such as hypotension and bradycardia with increased dosage, along with its effects such as sedation and anxiolysis 14 . In this study the incidence of bradycardia was high, despite the absence of hypotension in the RD group.…”
Section: Discussionmentioning
confidence: 99%